Perubahan antropometri, kalsium darah, tekanan darah, dan kebugaran fisik akibat asupan susu kambing pada olahragawan - Yusni Yusni; Amiruddin Amiruddin (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Changes in anthropometry, blood calcium, blood pressure, and physical fitness due to goat's milk intake in athletesBackground: The intake of healthy-balanced nutrition is needed by athletes. The complex nutritional content of goat milk such as protein, fat, carbohydrate, vitamin, and mineral acts as sports nutrition during and after training. Objective: This study aims to analyze the effects of goat milk on physical fitness, anthropometrics, blood calcium, and blood pressure in athletes. Methods: A clinical trial was conducted using healthy human subjects. Subjects were runners (n=10 people) as the control group and gymnasts (n=19 people) as the treatment group, male, age 21-27 years, and healthy. Bodyweight (BW), Height, and Body Mass Index (BMI), blood calcium, Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP), and physical fitness were examined two times, before and after consuming goat milk. Intervention: fresh goat milk, 250 mg/day (after dinner), and given for 90 days. Data were analyzed using a paired sample t-test and independent sample t-test. Results: There was no difference between BW (p=0.07), BMI (p=0.08), and DBP (p=0.24), but instead there was a significant difference in SBP (p=0.00) before and after goat milk intervention in the experimental group. Blood calcium was significantly increased (p=0.00) in the intervention group, whereas reverse decreased significantly (p=0.02) in controls. A significant difference before and after therapy was found in speed (p=0.00), arm muscle endurance (p=0.01), an-aerobic endurance (p=0.00), agility (p=0.02), however, there was no significant difference between leg muscle power (p=0.13), flexibility (p=0.23), an endurance of abdominal muscles (p=0.26), VO2 max (p=1.15) in the intervention group. Conclusions: Regular consumption of goat milk can reduce SBP, increase blood calcium levels, and improve physical fitness (speed, arm muscle endurance, anaerobic endurance, and agility) in athletes. Goat milk is an essential role in sports nutrition for physical fitness and athlete's health.